2016
DOI: 10.2217/nnm-2016-0047
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles Coated with High Molecular Weight PEG Penetrate Mucus and Provide Uniform Vaginal and Colorectal Distribution in Vivo

Abstract: Aims We previously demonstrated that nanoparticles (NPs) densely coated with low molecular weight (MW, 2-5 kDa) polyethylene glycol (PEG) rapidly diffused through various mucus secretions, whereas NPs coated with 10 kDa PEG were mucoadhesive due to presumed polymer interpenetration and entanglement with mucins. Here, we demonstrate that PEG with MW as high as 40 kDa can be used as a mucoinert NP surface coating if sufficient surface density is achieved. Materials and Methods We compared two sets of reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(71 citation statements)
references
References 31 publications
4
67
0
Order By: Relevance
“…47,156,157 In addition, recently Maisel et al (2016) recently showed that PEG molecular weights as high as 40 kDa can be used for mucus penetration, with higher molecular weights requiring extremely high PEGylation density to reduce entanglements. 158 …”
Section: Selective Transport Of Objects On the Order Of Mesh Sizementioning
confidence: 99%
“…47,156,157 In addition, recently Maisel et al (2016) recently showed that PEG molecular weights as high as 40 kDa can be used for mucus penetration, with higher molecular weights requiring extremely high PEGylation density to reduce entanglements. 158 …”
Section: Selective Transport Of Objects On the Order Of Mesh Sizementioning
confidence: 99%
“…designed polystyrene NPs densely coated with low‐molecular‐weight polyethylene‐glycol to prevent interaction with the mucus, which enhanced NP penetration. This NP formulation was capable of rapidly crossing the mucosal layer in a mouse model …”
Section: Microbicide Dosage Formsmentioning
confidence: 99%
“…The mucus at the mucosal surface of the FGT can hinder viral movement but can also slow down NPs crossing the mucosal barrier into the submucosa. Maisel et al 46 designed polystyrene NPs densely coated with low-molecular-weight polyethylene-glycol to prevent interaction with the mucus, which enhanced NP penetration. This NP formulation was capable of rapidly crossing the mucosal layer in a mouse model.…”
Section: Nanotechnology-based Systemsmentioning
confidence: 99%
“…Our group has focused on the production of nanoparticles composed of a polyethylene glycol diacrylate (PEGDA)–n‐vinyl pyrrolidone (NVP) crosslinked hydrogel matrix encapsulated with phosphate salts and synthesized using an inverse miniemulsion polymerization process . Polyethylene glycol (PEG)‐coated nanoparticles, or PEGylated nanoparticles have demonstrated significant promise in drug delivery research as their surface does not promote non‐specific tissue binding while allowing for deeper penetration and longer circulation times especially in mucosal tissues . However, it must be noted that in these prior studies the nanoparticles investigated were composed of different material structures (linear polymers or crystalline materials ) and subsequently surface‐coated with PEG.…”
Section: Introductionmentioning
confidence: 99%
“…Polyethylene glycol (PEG)‐coated nanoparticles, or PEGylated nanoparticles have demonstrated significant promise in drug delivery research as their surface does not promote non‐specific tissue binding while allowing for deeper penetration and longer circulation times especially in mucosal tissues . However, it must be noted that in these prior studies the nanoparticles investigated were composed of different material structures (linear polymers or crystalline materials ) and subsequently surface‐coated with PEG. The development of crosslinked hydrogel PEG nanoparticles for drug delivery applications is rare.…”
Section: Introductionmentioning
confidence: 99%